Effect of Solvents on Selective Molecularly Imprinted Solid-Phase Extraction of Enrofloxacin from Fish Samples - Lv, Yun-Kai; Wang, Li-Min; Zhao, Mi-Ge; Zhang, Jing-Qi; Sun, Han-Wen (Asian Journal of Chemistry, 2012)
A sample preparation method of solid-phase extraction using a molecularly imprinted polymer as selective adsorbent for the enrofloxacin has been developed. The conditioning, loading, washing and eluting solvents were investigated and evaluated by the recovery and retention of enrofloxacin to obtain the optimum conditions of the molecularly imprinted solid-phase extraction (MISPE). Under the optimal solid phase extraction condition, three fluoroquinolones residues in fish were separated and detected by an off-line MIP-SPE-HPLC with better clean-up and enrichment.